Medicinal Formula Huazhi-Rougan Attenuates Non-Alcoholic Steatohepatitis Through Enhancing Fecal Bile Acid Excretion in Mice - Li, Chunlin; Yu, Siyu; Li, Xiaoxiao; Cao, Ying; Li, Meng; Ji, Guang; Zhang, Li (Frontiers in Pharmacology, 2022)
Huazhi-Rougan (HZRG) formula is a Traditional Chinese medicine prescription, and has been widely used to treat non-alcoholic fatty liver disease (NAFLD) and its progressive form non-alcoholic steatohepatitis (NASH). However, the anti-NASH effects and the underlying mechanisms of HZRG have not yet been characterized. Here we showed that 4-week HZRG treatment alleviated methionine-choline-deficiency (MCD) diet-induced NASH in C57BL/6J mice, as evidenced by the improvement of hepatic steatosis and inflammation, as well as the decrease of serum levels of alanine and aspartate transaminases. Fecal 16S rDNA sequencing indicated that HZRG reduced the enrichment of pathogenic bacteria and increased the abundance of bacteria gena that are involved in bile acid (BA) conversation. The alteration of fecal and serum BA profile suggested that HZRG enhanced fecal BA excretion, and reduced the reabsorption of toxic secondary BA species (LCA, DCA, HCA). We further analyzed the BA receptors and transporters, and found that HZRG inhibited the expression of ileal bile acid transporter, and organic solute transporter subunit β, and increased the expression of intestinal tight junction proteins (ZO-1, Occludin, Claudin-2). The modulation of gut dysbiosis and BA profile, as well as the improvement of the intestinal environment, may contribute to the decrease of the p-65 subunit of NF-κB phosphorylation, liver F4/80 positive macrophages, inflammatory cytokine IL-1β and TNF-α expression. In conclusion, HZRG treatment enhances fecal BA excretion via inhibiting BA transporters, modulates BA profiles, gut dysbiosis as well as the intestinal environment, thus contributing to the beneficial effect of HZRG on NASH mice.